Linked-read Sequencing Analysis Reveals Tumor-specific Genome Variation Landscapes in Neurofibromatosis Type 2 (NF2) Patients. Issue 2 (February 2019) - Roberts, Daniel S.; Maurya, Rahul; Takemon, Yuka; Vitte, Jeremie; Gong, Liang; Zhao, Juanjuan; Wong, Chee-Hong; Slattery, William; Peng, Kevin A.; Lekovic, Gregory; Schwartz, Marc S.; Bulsara, Ketan; et al.
Abstract : Hypothesis: We hypothesize that genomic variants including deletions, insertions, inversions, and tandem duplications beyond the changes in tumor suppressor NF2 gene affect gene expression of tumor-specific pathways in vestibular schwannomas (VS) patients with Neurofibromatosis type 2 (NF2), thus contributing to their clinical behavior. Background: Genomic variation could reconfigure transcription in NF2 transformation process. Therefore, genome-wide high-resolution characterization of structural variants (SV) landscapes in NF2 tumors can expand our understanding of the genes regulating the clinical phenotypes in NF2-associated VS. Methods: We performed whole-genome haplotype-specific structural variation analysis using synthetic linked reads generated through microfluidics-based barcoding of high molecular weight DNA followed by high-coverage Illumina paired-end whole-genome sequencing from 10 patients' tumors of different growth rates and their matching blood samples. Results: NF2 tumor-specific deletions and large SVs were detected and can be classified based on their association with tumor growth rates. Through detailed annotation of these mutations, we uncover common alleles affected by these deletions and large SVs that can be associated with signaling pathways implicated in cell proliferation and tumorigenesis. Conclusion: The genomic variation landscape of NF2-related VS was investigated through whole-genome linked-read sequencing. Large SVs, in addition to deletions, were identified and may serve as modulators of clinical behavior. Abstract : Supplemental Digital Content is available in the text